Analisis Perilaku Golput Dikalangan Masyarakat Dan Aspek Hukum Golput Dalam Pelaksanaan Pemilihan Umum - Jayanti, Wilda Dwi; Putri, Vianka Maulidya (Jurnal Ilmiah Wahana Pendidikan, 2024)
In the implementation of general elections in Indonesia, there is always the involvement of white-skinned voters, commonly referred to as "Golput," which is a term used to describe the act of abstaining from voting during elections. This behavior within the community has its advantages and disadvantages as it is believed to have an impact on the development and progress of democracy in Indonesia. The fundamental definition of Golput is the act of not exercising one's freedom to vote in elections due to various factors and arguments. Dissatisfaction among citizens with political institutions is considered unequal in decision-making, and this is the root cause of the increasing trend of not voting (Golput) in elections. According to data from the General Election Commission (KPU), there is still a significant number of Golput instances among the population. Therefore, a plan or strategy is needed to address this issue, which involves expanding the understanding and education of all citizens about the importance of voting as an obligation that must be fulfilled by all members of society. In this regard, there are no legal penalties for the act of Golput as found in the laws, but those who incite or encourage others not to exercise their right to vote may face the possibility of receiving punishment for their actions.